2012
DOI: 10.1126/science.1216171
|View full text |Cite
|
Sign up to set email alerts
|

An Early-Branching Microbialite Cyanobacterium Forms Intracellular Carbonates

Abstract: Cyanobacteria have affected major geochemical cycles (carbon, nitrogen, and oxygen) on Earth for billions of years. In particular, they have played a major role in the formation of calcium carbonates (i.e., calcification), which has been considered to be an extracellular process. We identified a cyanobacterium in modern microbialites in Lake Alchichica (Mexico) that forms intracellular amorphous calcium-magnesium-strontium-barium carbonate inclusions about 270 nanometers in average diameter, revealing an unexp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
218
1
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 216 publications
(229 citation statements)
references
References 35 publications
8
218
1
2
Order By: Relevance
“…One striking observation is that aragonite appears recurrently associated with one predominant type of cyanobacteria having the typical morphology of Pleurocapsales (Figures 4-6 and Supplementary Figures S3, S4 and S5). So far, few studies have suggested that some species could be specifically associated with mineral precipitation within the complex diversity of a biofilm (for example, Planavsky et al, 2009, Couradeau et al, 2012. Here we show that a specific lineage of cyanobacteria can orient carbonate precipitation towards aragonite, whereas hydromagnesite precipitates elsewhere.…”
Section: Discussionmentioning
confidence: 71%
See 1 more Smart Citation
“…One striking observation is that aragonite appears recurrently associated with one predominant type of cyanobacteria having the typical morphology of Pleurocapsales (Figures 4-6 and Supplementary Figures S3, S4 and S5). So far, few studies have suggested that some species could be specifically associated with mineral precipitation within the complex diversity of a biofilm (for example, Planavsky et al, 2009, Couradeau et al, 2012. Here we show that a specific lineage of cyanobacteria can orient carbonate precipitation towards aragonite, whereas hydromagnesite precipitates elsewhere.…”
Section: Discussionmentioning
confidence: 71%
“…Under these conditions, the precipitation of hydromagnesite (Mg 5 (CO 3 )4(OH)2 þ 4H 2 O), which is the dominant carbonate mineral in microbialites, is naturally favored (Kaźmierczak et al, 2011). Alchichica microbialites harbor a wide diversity of cyanobacteria, among which members of the Oscillatoriales and Pleurocapsales are the most abundant, but also members of many other prokaryotic and eukaryotic lineages are present (Couradeau et al, 2011(Couradeau et al, , 2012.…”
Section: Introductionmentioning
confidence: 99%
“…Their most conspicuous characteristic is the accumulation of numerous large inclusions filling the majority of the cell that were first described as calcium oxalate, giving the type species Achromatium oxaliferum its name, but which were later recognized as colloidal calcite (West and Griffiths, 1913;Bersa, 1920;Head et al, 1996). Recently, cyanobacteria (Gloeobacterales) were found to form amorphous calcium-magnesium-strontium-barium carbonate inclusions (Couradeau et al, 2012); however, the massive accumulation of CaCO 3 in Achromatium is still a unique peculiarity in the microbial world (Head et al, 2000;Gray and Head, 2014). The biological function of internal calcite is under investigation, and hypotheses include its usage as buffer, a source of CO 2 or a mechanism of buoyancy regulation (Gray, 2006, reviewed in Head et al, 2000.…”
Section: Introductionmentioning
confidence: 99%
“…A late emerging violet clade is consistent with the inclusion of Synechococcus sp. JA-2-3B′A and JA-3-3AB in the order Gloeobacterales based on sequences from a recently cultured early branching cyanobacteria (26). #sp., number of genomes.…”
mentioning
confidence: 99%